2007
DOI: 10.1007/s10551-007-9382-8
|View full text |Cite
|
Sign up to set email alerts
|

Local Responsiveness Pressure, Subsidiary Resources, Green Management Adoption and Subsidiary’s Performance: Evidence from Taiwanese Manufactures

Abstract: green management, MNCs, performance, resource, stakeholders,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
128
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(138 citation statements)
references
References 29 publications
(51 reference statements)
1
128
1
2
Order By: Relevance
“…Such firms may also incur reduced risk of environmental liabilities, potentially limiting their associated insurance and legal costs and even lowering their cost of capital (e.g., Christmann 2004). To the extent that sustainability issues are important to employees, firms with green marketing programs may also benefit from increased employee morale and output, enhancing productivity (Menon et al 1999;Peng and Lin 2008). Green marketing programs may also result in higher revenues.…”
Section: The Role Of Top Management Risk Aversionmentioning
confidence: 99%
“…Such firms may also incur reduced risk of environmental liabilities, potentially limiting their associated insurance and legal costs and even lowering their cost of capital (e.g., Christmann 2004). To the extent that sustainability issues are important to employees, firms with green marketing programs may also benefit from increased employee morale and output, enhancing productivity (Menon et al 1999;Peng and Lin 2008). Green marketing programs may also result in higher revenues.…”
Section: The Role Of Top Management Risk Aversionmentioning
confidence: 99%
“…Several studies have showed the positive financial effect of environmental management (Florida & Davison, 2001;Barnett & Salomon, 2006;Peng & Lin, 2008). In this stream, corporate eco-friendly efforts can create proactive intangible assets and dynamic capabilities that contribute to improved firm performance (Russo & Fouts, 1997;Teece, 2007;Mzembe et al, 2016).…”
Section: Issues and Hypotheses Developmentmentioning
confidence: 99%
“…First, the perceived importance of environment improvement by managers negatively affect to innovation performance. It is quite surprising because most of the previous literature pointed out that innovation improving environment leads to higher firm performance [37,[39][40][41][42][43]. Given that previous literature considered the output only, however, the result of this study does not counter the literature, but rather point to the possibility that the input that is required to perform environmental innovation is much higher than the actual output transformed from it.…”
Section: Resultsmentioning
confidence: 54%
“…Diverse studies found out the positive effect of green innovation on firm performance, such as material or energy reduction and environmental improvement [39][40][41][42][43][44]. In a similar vein, environmental marketing is found to affect positively to firms' capabilities [45,46].…”
Section: Sustainable Innovationmentioning
confidence: 97%